Improving Students' Mathematical Communication Ability Through Problem-Based Learning Assisted By Baamboozle - Kajori, Febbyana Ilwan; Hendriana, Benny (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
Mathematical communication ability is a must-have ability for students but several studies show students' communication ability are still low. This study aims to improve students' mathematical communication ability through Problem-Based Learning assisted by Baamboozle in opportunity material. Baamboozle is an learning media that helps teachers to present an outline of material concepts, increases students' sense of cooperation to gain knowledge and makes learning activities more enjoyable. The subject of this study was located at one of the South Jakarta State Senior High Schools in class X-4 with a total of 33 students. The classroom action research method was chosen as a research method that adapts the Kemmis and Taggart methods. Data were collected using tests, and analyzed descriptively qualitatively. The results of the study revealed a rise in the percentage of students who had high-level of mathematical communication ability in each cycle, in the first cycle recording 63.64% and in the second cycle recording 78.79%. Therefore, Problem-Based Learning assisted by Baamboozle can improve ability of mathematical communication and make learning activities more active and fun.